Quantifying ocular microcirculation in hypertension patients with carotid artery stenosis - Ma, Jinlan; Gelie, NanJia; Zhu, Mingjuan; Ma, Xiaolu; Han, Changjing (Frontiers in Neuroscience, 2024)
Background Carotid artery stenosis (CAS) is one of the most common macrovascular complications of hypertension. The ophthalmic artery springs from the internal carotid artery; however, the effect of CAS on ocular microcirculation has not been quantified in hypertension patients. This study aimed to quantify ocular microcirculation metrics in hypertension with CAS (HCAS) patients and to explore the relationship between micro- and macroangiopathy in hypertension. Methods All participants (community-based) underwent detailed assessments, including carotid ultrasonography, optical coherence tomography angiography (OCTA), and enhanced depth imaging (EDI)-OCT. CAS was diagnosed using carotid ultrasonography. Retinal microcirculation metrics, including vessel density (VD), skeleton density (SD), fractal dimension (FD), and foveal avascular zone (FAZ), were quantified using OCTA and ImageJ software. Choroidal microcirculation metrics, including subfoveal choroidal thickness (SFCT), luminal area (LA), and choroidal vascularity index (CVI), were quantified using EDI-OCT and ImageJ. Retinal vessel caliber metrics, including central retinal artery equivalent (CRAE), central retinal vein equivalent (CRVE), and artery/vein ratio (AVR), were calculated using revised formulas. The above metrics were compared among the HCAS group, hypertension with no CAS (HNCAS) group, and healthy control group. The mutual effects between ocular metrics and CAS were evaluated using regression analyses. Results In a comparison of the HCAS vs. HNCAS groups, retinal metrics including VD, SD, FD, and choroidal metrics including CVI and LA were significantly decreased in the HCAS group (all p < 0.05); however, FAZ, SFCT, and retinal vessel caliber metrics including CRAE, CRVE, and AVR were comparable between groups (all p > 0.05). In a comparison of HNCAS and the healthy control group, VD, SD, and CRAE showed that AVR was significantly decreased in the HNCAS group (all p < 0.05); meanwhile, choroidal metrics were comparable between groups (all p > 0.05). Linear regression analyses showed that intima-media thickness (IMT) (p = 0.01) and peak systolic velocity (PSV) (p = 0.002) were negatively related to retinal VD in hypertension patients. Logistic regression analyses disclosed that older age (p < 0.001), smoking history (p = 0.002), lower VD (p = 0.04), SD (p = 0.02), and CVI (p < 0.001) were related to the presence of CAS in hypertension patients. Conclusion CAS in hypertension-induced hypoperfusion in retinal and choroidal microcirculation and the decreased retinal VD and choroidal CVI were significantly associated with the presence of CAS in patients with hypertension, suggesting that hypertension macro- and microangiopathy were mutually affected and share the common pathophysiology. Furthermore, OCT could be a useful tool to assess hypertension patient’s CAS risk profiles in a non-invasive way.